REKRUTMEN DAN PENEMPATAN PEGAWAI - Andrizul '; Yoserizal ' (Jurnal Kebijakan Publik, 2013)
This study aims to analyze the recruitment andplacement of personnel in the Office of the District Kesahatan Singingi Kuantan. Data collectedby interview and observation techniques, after the data was collected and then analyzed usingqualitative descriptive analysis. The results showed that the analysis of the recruitment andplacement of personnel in the Department Kesahatan Singingi Regency Kuantan is not good.While found factors that hinder the analysis of employees in Kuantan District Health Singingi,the coordination factor, the factor of transparency and financial factors.